ART AS COMMUNICATION IN HOTSPOTS OF THE PLANET (ON THE EXAMPLE OF MODERN SYRIA). PART ONE - Oksana Kosiuk (Інтегровані комунікації)
The article proves that in the context of coverage of global geopolitical catastrophes, the problem of unambiguous representation of facts is becoming more and more urgent since each of the participants in the conflict defends their views on the causes, consequences and unfolding of events. Moreover, the mass media rebroadcast the information conflict, completely disorienting the recipients. It is easy to see by looking at how the media of America, Iran, Britain, France, and Israel show the war in Syria: the same event is completely unrecognizable in their situational coverage.